Flexural performance of built-up cold-formed steel beam (CFSB) filled with concrete - Jarrud Mohamed, Muftah Mohamed (2022)
Cold-formed steel (CFS) became more visible in the construction field with noticeable advantages such as cost-effectiveness, lightweight, easy instalment, low maintenance and corrosion resistance, easily transportable, recyclable, and easy fabrication compared to hot-rolled steel sections. However, the CFS section's associated failure modes, such as local, distortional, lateral-torsional, and global buckling, impeded their application in the construction industry. Therefore, built-up closed CFS beam sections have been introduced with low-cost material such as concrete to mitigate local buckling failure modes and enhance strength and ductility. Prior studies in this line have mainly concentrated on the performance of CFS beams in terms of compression, with the flexural aspect primarily ignored. More importantly, the CFS beam flexural analysis is more complicated in terms of design and failure mode shape. Therefore, this study aimed is to investigate the flexural performance of concrete-filled CFS beam tightened with three bolts using a 3D non-linear finite element analysis. ABAQUS software was used as the finite element tool in this study. The finite element modelling procedures were verified with two previous experimental findings based on the load-deflection response and the failure modes prior to the parametric study. The FE results based on three previous studies show reasonable simulation accuracy of the ultimate load capacity and the mode failures, hence the validation has been performed. Then, parametric study was conducted with six different bolt configurations to investigate the flexural performance of the concrete filled CFS composite beam. The findings of parametric study revealed that increasing the edge bolt spacing in the composite beam to a specific limit resulted in improved performance. Furthermore, filling the built-up CFS section with concrete eliminated any buckling failure modes associated with the CFS section. On the other hand, flexural cracking was the most common failure mode of the infill concrete, with minor concrete crushing at the bottom of the edge-bolt hole. Overall, the results obtained in terms of load capacity, failure modes, and stress development for the CFS built-up section beam tightened with bolts can provide engineers with insight into the various future application possibilities of these different components forming the composite beam and utilization for improving the methodological procedures in the CFS-concrete composite design.